Challenging Social Inequality : The Landless Rural Workers Movement and Agrarian Reform in Brazil - Carter, Miguel, 1964-; Carter, Miguel, 1964- (Book collections on Project MUSE., 2015)
In Challenging Social Inequality, an international and interdisciplinary group of scholars and development workers explores the causes, consequences, and contemporary reactions to Brazil's sharply unequal agrarian structure.